ANALYSIS OF FACTORS RELATED TO SELF CARE IN HYPERTENSION PATIENTS AT BANTIMURUNG HEALTH CENTER - Maryam Jamaluddin; Alfiah A; Yusnaeni Y (PT.Mantaya Idea Batara, 2023)
Hypertension is a major public health problem worldwide. Efforts to control hypertension are more cost effective through non-pharmacological approaches. Control of hypertension in beliefs can be done by controlling blood pressure which can be done by controlling a healthier lifestyle. To reduce and prevent complications from hypertension, it is important to adapt self-care behaviors. Self care has been recognized as an important and cost-effective aspect in the management and prevention of hypertension and its complications. The research objective in this study was to determine the relationship between sociodemographic factors and self care in hypertensive patients at the Bantimurung Public Health Center. This type of research uses descriptive analytic correlation with a cross sectional study approach. The research will be carried out at the Tamalanrea Makassar Health Center. The population in this study were all adults (18-45 years) and the sample was taken using consecutive sampling technique. Data collection used questionnaires and observation sheets and was processed by statistical tests with a significance level of p value <0.05. The results showed that there was a relationship between education and family support with self-care in hypertensive patients at the Bantimurung Health Center.